Akkermansia muciniphila Exerts Strain-Specific Effects on DSS-Induced Ulcerative Colitis in Mice - Liu, Qing; Lu, Wenwei; Tian, Fengwei; Zhao, Jianxin; Zhang, Hao; Hong, Kan; Yu, Leilei (Frontiers in Cellular and Infection Microbiology, 2021)
Akkermansia muciniphila is a commensal bacterium of the gut mucus layer. Although both in vitro and in vivo data have shown that A. muciniphila strains exhibit strain-specific modulation of gut functions, its ability to moderate immunity to ulcerative colitis have not been verified. We selected three isolated human A. muciniphila strains (FSDLZ39M14, FSDLZ36M5 and FSDLZ20M4) and the A. muciniphila type strain ATCC 835 to examine the effects of different A. muciniphila strains on dextran sulfate sodium-induced colitis in mice. Only A. muciniphila FSDLZ36M5 exerted significant protection against ulcerative colitis (UC) by increasing the colon length, restoring body weight, decreasing gut permeability and promoting anti-inflammatory cytokine expression. However, the other strains failed to provide these effects. Notably, A. muciniphila FSDLZ20M4 showed a tendency to exacerbate inflammation according to several indicators. Gut microbiota sequencing showed that A. muciniphila FSDLZ36M5 supplementation recovered the gut microbiota of mice to a similar state to that of the control group. A comparative genomic analysis demonstrated that the positive effects of A. muciniphila FSDLZ36M5 compared with the FSDLZ20M4 strain may be associated with specific functional genes that are involved in immune defense mechanisms and protein synthesis. Our results verify the efficacy of A. muciniphila in improving UC and provide gene targets for the efficient and rapid screening of A. muciniphila strains with UC-alleviating effects.